2004
DOI: 10.4049/jimmunol.172.4.2578
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Mediated Inhibition of Neutrophil Transmigration by Blocking CD47 Interactions with Signal Regulatory Protein α

Abstract: CD47, a cell surface transmembrane Ig superfamily member, is an extracellular ligand for signal regulatory protein (SIRPα). Interactions between CD47 and SIRPα regulate many important immune cell functions including neutrophil (PMN) transmigration. Here we report identification of a novel function-blocking peptide, CERVIGTGWVRC, that structurally mimics an epitope on CD47 and binds to SIRPα. The CERVIGTGWVRC sequence was identified by panning phage display libraries on the inhibitory CD47 mAb, C5D5. In vitro P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…In support of our observation, a study suggested that a high IL-10 level may be an indicator of disease progression and severity (46). Defective neutrophil migration was observed in the absence of CD47 expression (13). A deficiency or blockade of CD47 is protected from lipopolysaccharide (LPS)-induced acute inflammatory disease and Th2-driven airway inflammation by inhibiting the migration of leukocytes and neutrophils, respectively (44,47).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In support of our observation, a study suggested that a high IL-10 level may be an indicator of disease progression and severity (46). Defective neutrophil migration was observed in the absence of CD47 expression (13). A deficiency or blockade of CD47 is protected from lipopolysaccharide (LPS)-induced acute inflammatory disease and Th2-driven airway inflammation by inhibiting the migration of leukocytes and neutrophils, respectively (44,47).…”
Section: Discussionsupporting
confidence: 74%
“…SIRP␣ is also expressed on dendritic cells (DCs) and macrophages, whereas SIRP␣ is barely expressed on B and T cells (11,12). It has been demonstrated that CD47/CD47 and CD47/SIRP␣ interactions are important for DC and neutrophil migration (13,14). In addition, CD11b ϩ DCs in the lungs express both CD47 and SIRP␣, but CD103 ϩ DCs express only CD47.…”
mentioning
confidence: 99%
“…A murine polyclonal antibody specific to SIRP␣ was generated by immunizing mice with a fusion protein consisting of the extracellular domain of human SIRP␣1 (Ig loops 1 ϩ 2 ϩ 3) fused to rabbit Fc (SIRP␣1.ex-Fc) (18). Monoclonal antibodies B4B6 and B1D5 that specifically bind to SIRP␤ were generated as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 2A, two CAR-GST recombinants (CAR1 ϩ 2-GST: AA 1-240; CAR1-GST: AA 1-134) and three JAML-Fc recombinants (JAML1-Fc: AA 1-130; JAML2-Fc: AA 141-256; JAML1 ϩ 2-Fc: AA 1-256) were prepared, accordingly. In the experiments, recombinant CD47 and SIRP␣1 extracellular domain fusion proteins CD47-alkaline phosphatase (AP) and SIRP␣-GST were produced as described previously (Seiffert et al, 1999;Liu et al, 2002Liu et al, , 2004a. …”
mentioning
confidence: 99%